Pengaruh Pembiayaan KUR Mikro Bank Syariah terhadap Perkembangan UMKM: Peran Syari’ah Compliance sebagai Variabel Moderasi - Oktavia, Rizka Dwi; Syahbudi, Muhammad; Inayah, Nurul (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2025)
Micro, Small, and Medium Enterprises (MSMEs) are a critical pillar of the economy in Indonesia, yet they often face fundamental obstacles in accessing effective and affordable financing, which hinders their growth potential. This study aims to deeply analyze the influence of the Micro Business Credit (KUR) program, distributed by Bank Aceh Syariah, on the development of MSMEs in Medan City. Furthermore, this study also assesses the strategic role of Shariah Compliance as a moderating variable presumed to strengthen this relationship. Using a quantitative method with a survey approach, primary data were collected from 35 respondents selected via purposive sampling out of a total of 500 KUR recipients. Data analysis was conducted comprehensively using SPSS, encompassing validity and reliability tests, descriptive analysis, simple linear regression, and Moderated Regression Analysis (MRA). The research findings indicate that KUR has a positive and significant impact on the development of MSMEs. The Shariah Compliance variable was also found to significantly strengthen this relationship, as indicated by an increase in the coefficient of determination from 78.5% to 88.3% after the inclusion of the moderating variable. This finding confirms that sharia-based financing not only enhances financial access but also strengthens the business fundamentals of MSMEs.